EFFECTIVENESS OF MAGNETIC THERAPY FOR LUMBAR SPINE OSTEOCHONDROSIS IN MILITARY PERSONNEL - Kamalova Z.S., Khamrabayeva F.I. (Central Asian Journal of Medicine, 2025)
We treated 110 military personnel with reflex syndromes of spinal osteochondrosis. Of these, 64 (58%) are men, 46 (42%) are women. The control group consisted of 10 patients with lumbar osteochondrosis who received only drug therapy. Magnetic therapy was applied to 20 patients with reflex syndromes of lumbar osteochondrosis against the background of conservative therapy. The obtained treatment results were assessed directly at the end of the course of treatment and in the long-term period. When exposed to electromagnetic radiation, no significant reduction in functional blockades in the spinal motor segments was observed. Neurodystrophic manifestations tended to level out during the course of treatment, which was manifested by activation of blood circulation. A positive result was achieved in 63% of cases (19 patients). Deterioration was noted in 1 patient, in whom a protrusion of the intervertebral disc at the level of L5-S1 was detected as a result of computed tomography. The condition of 2 patients (7%) with pronounced pseudo-spondylolisthesis remained unchanged. Therefore, we can talk about the effect of magnetotherapy on the state of hemodynamics and water balance of the body, which indirectly indicates the activation of not only arterial inflow, but primarily venous-lymphatic outflow.